Intralingual and Interlingual Grammatical Error Analysis on Students’ Writing - Kusmaryani, Woro; Fitriawati, Fitriawati (Universitas Muhammadiyah Mataram, 2023)
This article is intended to reveal students’ Intralingual and Interlingual Grammatical Error on their writings. The design of this research was descriptive qualitative. This research was conducted at Junior High School Level with 21 participants through purposive sampling method. Students’ writings were the main data used in this research. Based on the students' writings, the researchers pinpointed the errors' sources. Using Richards' categorization, the errors were then divided into intralingual transfer and interlingual transfer. Intralingual transfer was the first and most frequent source of errors. This type contained 66 errors, or 84%. Interlingual error was the second most common type of error, accounting for 13 or 16% of all errors. The target language itself, which led to the students' errors. Interlingual error occurred when students employed the first language system to produce language because they were unaware of the rules or grammar of the target language they were learning. It is crucial for teachers explain to students how grammatical notions function in context. Giving constructive feedback on English grammar assignments will enable teachers and students to gain a better idea of where each person sits in terms of their knowledge level.